SOCIAL IMPACT OF FINANCIAL TECHNOLOGY AND ISLAMIC ECONOMICS EDUCATION: - - Basrowi, basrowi (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2021)
The purpose of this study is to test hypotheses about how the impact of financial technology (Fintech) and Islamic economic education in improving social welfare. Correlational quantitative research was chosen to reveal the social impact of the two variables. The research population is all people in Lampung Province, Indonesia who are educated in Islamic economics, who at the time of the study were at least sitting in the fifth semester undergraduate program. The sample is 308 people or 10% of the population of 3080 people. Data were collected using a questioner that was shared using Google Form. Data analysis was performed using a structural equation model (SEM) approach with the Lisrel 8.80 program. The results showed that, the social impact of utilizing financial technology and Islamic economic education includes two aspects, namely positive and negative impacts which are all related to people's economic behavior, economic learning, and psychological and spiritual health. Positive impacts dominate more than negative impacts.